(untitled) (Bangladesh Medical Journal, 2016)
Adrenoleukodystrophy (ALD) is a peroxisomal disorder characterized by the accumulation of saturated very long chain fatty acids (VLCFA) in plasma, various tissues of body and central nervous system. It causes demyelination and adrenocortical insuciency. High levels of very long chain fatty acids are found in tissues and body fluids, resulting from their impaired ?-oxidation in the peroxisomes. The most common form of ALD is an X-linked disorder with various presentations which is caused by mutations in the ABCD1 gene located on Xq28. The gene encodes a transmembrane transporter involved in the importation of very long chain fatty acids into peroxisomes. The phenotypic presentations are highly variable, which may lead to delayed recognition and misdiagnosis, as attention deficit and/or hyperactivity disorder in boys or multiple sclerosis in adults. The most common clinical picture is of a degenerative neurologic disorder appearing in childhood or adolescence and progressing to severe dementia and deterioration of vision, hearing, speech, and gait and death occur within a few years. Many patients have evidence of adrenal insufficiency at the time of neurologic presentation. Hydrocortisone and mineralocorticoid are necessary to treat adrenal insufficiency. High doses of hydrocortisone preoperatively and during recovery are needed for surgery and other stressful illnesses in affected individuals. Here, we described two patients with childhood onset ALD with clinical and laboratory features to illustrate the wide clinical variability of this condition. Bangladesh Med J. 2015 Sep; 44 (3): 168-171